2012
DOI: 10.1177/1010539512446368
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Obesity Research in the Asia-Pacific

Abstract: Obesity is a global health concern and has a great impact on countries in the Asia-Pacific region. Physical inactivity is a major risk factor for obesity, but physical activity levels are declining in much of this region. Increasing physical activity is a priority in many countries. Considerable research has been conducted on physical activity related to obesity in Western countries, but populations in the Asia-Pacific region differ in physical, psychological, social, and cultural ways that warrant local and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…This school is a private Catholic school that attracts children largely from the middle class with at least one parent educated to university level and at least one parent in full employment. Manila has an area of 38.55 km 2 with a population of 1 660 714 as of 2007. Its economy is diverse and multifaceted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This school is a private Catholic school that attracts children largely from the middle class with at least one parent educated to university level and at least one parent in full employment. Manila has an area of 38.55 km 2 with a population of 1 660 714 as of 2007. Its economy is diverse and multifaceted.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of childhood obesity around the world has steadily increased in the past decade to the point where it is an alarming new public health problem not only in Western countries but also in the Asian region. 1-3 Childhood obesity is associated with the development of fatty liver and type 2 diabetes mellitus in adolescents. Unless addressed early, childhood obesity sets an individual on a lifetime track of obesity and is predictive of adult hypertension, diabetes mellitus, and coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) is an important outcome as reflecting the multifaceted dimension in obesity. 6,7 Previous studies reported that HRQoL in women was lower than that of men; this trend was shown not only in healthy people but also in patients receiving medical treatment. 8,9 The HRQoL of patients with severe diseases was found to be lower in women compared to men.…”
Section: Introductionmentioning
confidence: 97%
“…For high-income countries (e.g. Singapore, Hong Kong, Korea), the epidemiological transition is in full swing and we see a clear shift from communicable to non-communicable diseases (Khoo and Morris 2012). In low- and middle-income countries, a “double burden” is being faced of both communicable to non-communicable diseases (e.g.…”
Section: Changing Health Needs In the Asia And The Pacific Regionmentioning
confidence: 99%